Development of yttrium-containing self-passivating tungsten alloys for future fusion power plants. (December 2016) - Wegener, T.; Klein, F.; Litnovsky, A.; Rasinski, M.; Brinkmann, J.; Koch, F.; Linsmeier, Ch.
Highlights: Yttrium improves the self-passivation of the investigated W-Cr-Y alloys. Yttrium reduces the oxidation rates by one order of magnitude compared to the W-Cr system. The effects of yttrium are the suppression of mixed oxides and pores. The optimal composition found in this study is of W- 12 wt.%Cr-0.6 wt.%Y. An idealized simulation shows that the loss of alloying elements due to diffusion and sputtering is small. Abstract: Tungsten is a prime material candidate for the first wall of a future fusion reactor. In the case of a loss-of-coolant accident (LOCA) wall temperatures of about 1450 K could be reached lasting about 30–60 days due to nuclear decay heat. In the worst case scenario combining LOCA with air ingress, the formation and release of highly volatile and radioactive tungsten trioxide (WO3 ) into the environment can occur. Smart self-passivating tungsten alloys preventing the formation of WO3 can be a way to mitigate this release. In this contribution we present the studies of a new yttrium-containing W-Cr-Y alloys. The extent up to which yttrium acts as an active element improving the adherence and stability of the protective Cr2 O3 layer formed during oxidation is assessed. The approach is similar to the one taken for high-temperature steels where active elements stabilize the oxide layers at a substantially reduced thickness by changing the oxygen diffusion and improving the adherence of the protective oxide layer by e.g. avoiding of pores. Further, simulations on mobilized material for the case of a LOCA are developed. In addition, the loss of alloying elements during normal operation of a reactor is estimated. This is done by modelling a thermally activated diffusion, using a diffusion coefficient which is extrapolated from experimental data at higher values. The oxidation behaviour of magnetron sputtered and therefore alloyed at the atomic level W-Cr-Y alloys is tested in a thermo-gravimetric facility. The isothermal oxidations are performed in a gas mixture, containing 20 kPa oxygen and 80 kPa argon under ambient pressure at temperatures of 1273 K and 1473 K, respectively. Experiments with W-Cr-Y show a parabolic oxidation rate of k p = 3 · 10 − 6 mg 2 cm − 4 s − 1 which is more than five orders of magnitude lower than that of pure tungsten at 1273 K. Investigations using X-ray diffraction analysis and focused ion beam cross-sections in combination with scanning electron microscopy and energy dispersive X-ray spectroscopy are conducted. A protective Cr2 O3 layer is detected on the surface with a thickness between 100 and 300 nm.